2012
DOI: 10.1111/j.1365-2222.2012.04002.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to microbial agents in house dust and wheezing, atopic dermatitis and atopic sensitization in early childhood: a birth cohort study in rural areas

Abstract: Summary Background Early‐life exposure to environmental microbial agents may be associated with development of wheezing and allergic diseases. Objective To assess the association of microbial exposure in rural homes with the risk of asthma, wheezing, atopic dermatitis and sensitization. Methods Birth cohorts of rural children (n = 1133), half from farmer families, were followed up from birth to 2 years of age by questionnaires in five European centres. Endotoxin and extracellular polysaccharides (EPS) of Penic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 45 publications
(75 reference statements)
4
58
2
2
Order By: Relevance
“…The 'hygiene hypothesis', which posits that a lack of early childhood exposure to infectious agents increases susceptibility to allergic diseases, has been proposed as a possible explanation for this paradox (Strachan, 2000), although a consensus has yet to be reached. Despite the intriguing hypothesis, findings regarding the endotoxin-allergy relationship in adults and children have been inconsistent (Gehring et al, 2004;Karvonen et al, 2012;Liebers et al, 2006;Park et al, 2001;Thorne et al, 2005). Further study is required to clarify the role of endotoxin in the development of allergen tolerance and the influence of endotoxin on the sensitizing allergic response in the general population.…”
Section: Introductionmentioning
confidence: 93%
“…The 'hygiene hypothesis', which posits that a lack of early childhood exposure to infectious agents increases susceptibility to allergic diseases, has been proposed as a possible explanation for this paradox (Strachan, 2000), although a consensus has yet to be reached. Despite the intriguing hypothesis, findings regarding the endotoxin-allergy relationship in adults and children have been inconsistent (Gehring et al, 2004;Karvonen et al, 2012;Liebers et al, 2006;Park et al, 2001;Thorne et al, 2005). Further study is required to clarify the role of endotoxin in the development of allergen tolerance and the influence of endotoxin on the sensitizing allergic response in the general population.…”
Section: Introductionmentioning
confidence: 93%
“…It has been suggested that ongoing contact with livestock, contact with animal feed, and the consumption of unprocessed cow's milk during pregnancy and infancy might be particularly decisive for the observed protective effects [1]. Subsequently, the "farm environment" has been more specifically described by measuring microbial agents in settled house dust samples [2][3][4]. In this context, there is a common consensus that the time-window comprising pregnancy and early infancy seems to be crucial, where the biological diversity might have the potential to shape the child's immune response by upregulating the innate immunity receptors [1].…”
Section: Introductionmentioning
confidence: 99%
“…517 The risk of asthma is also reduced in children whose bedrooms have high levels of bacterial-derived lipopolysaccharide endotoxin. 518,519 Similarly, children in homes with ≥2 dogs or cats are less likely to be allergic than those in homes without dogs or cats. 503 Exposure of an infant to the mother's vaginal microflora through vaginal delivery may also be beneficial; the prevalence of asthma is higher in children born by Caesarian section than those born vaginally.…”
Section: Microbial Effectsmentioning
confidence: 99%